Peer-to-peer decentralized energy trading framework for retailers and prosumers - Mehdinejad, Mehdi; Shayanfar, Heidarali; Mohammadi-Ivatloo, Behnam (Applied energy, 2022)
The smart grid technology has increased the penetration of distributed energy resources by the development and expansion of communication infrastructures and thus arisen the need to redesign electricity markets. With the emergence of prosumers as smart agents capable of both producing and consuming energy, the modern electricity markets should be prosumer-centric. In the novel prosumer-centric approach, the prosumers can trade energy with each other in a peer-to-peer (P2P) fashion. In these new markets, the retailers can be thought of as profit-based companies that either generate electrical energy themselves or purchase it at variable prices from the wholesale market or other prosumers in the local market. The retailers then sell the generated or purchased energy to the local consumers, wholesale markets, or other prosumers. Smart grid technology allows the prosumers (the end-users) to purchase their needed power from any producer in the grid and sell their excess energy to any consumer or retailer. This article designs a competitive market consisting of prosumers and retailers such that all prosumers (as buyers and sellers) and retailers conduct peer-to-peer energy trading. A novel decentralized approach called primal–dual sub-gradient algorithm (PDSGA) is used to clear the designed market without third-party involvement or disclosure of players’ private information. The feasibility of the proposed market and the effectiveness of the novel decentralized scheme for market-clearing are demonstrated through numerical implementation. •Designs a competitive market consisting of prosumers and retailers.•A decentralized approach is proposed to clear the fully decentralized energy market.•Local players can bilaterally peer-to-peer interact with each other and retailers.•Market players have flexible generation and consumption.•Peer-to-peer energy trading is among all players.